Path Analysis on the Biopsychosocial Factors Affecting the Quality of Life in Patients with Breast Cancer - Rizka Amalia Dewi; Ambar Mudigdo; Eti Poncorini Pamungkasari (Journal of Epidemiology and Public Health, 2020)
Background: Breast cancer is the most com